Increasing innovativeness of SMEs in peripheral areas through international networks? The case of Southern Italy - Giuseppe Calignano; Robert Hassink (REGION, 2016)
Strengthening innovation capacity of European small and medium enterprises (SMEs) by means of their participation in the Sixth (FP6-SME) and Seventh (FP7-SME) Framework Programmes was an important objective of the European Union policies. Since SMEs form the backbone of the Italian economy, their strong presence in an international network such as the one fostered by the European Union represent a great opportunity, particularly for firms located in southern Italy - the marginal macro-area of the country in terms of innovation - to increase their competitiveness. Based on the major literature on topics such as knowledge exchange, innovation networks and disparities, and on descriptive statistics and a cluster analysis in a dynamic perspective, our study aimed to assess the actual intra-regional, extra-regional and transnational links established by the Italian SMEs and public research establishments (PREs). In a next step we aim at assessing if knowledge flows fostered by the FP6-SME and FP7-SME were mainly concentrated in the traditionally winning macro-regional areas (North and Centre) or led to more widespread benefits in favour of SMEs located in the marginal South. The findings of our study revealed a very limited number of connections - with a related weak knowledge exchange - involving the southern regions, implying a reinforcement of innovation activities in the traditionally most dynamic industrial areas of the country.
Keywords: 330; EU Policy; Knowledge Flows; Innovation Networks; Regional Disparites; SMEs